How Do Pre-service Elementary Teachers Notice Students' Algebraic Way of Thinking in Written Works? - Sümeyra DOĞAN COŞKUN (Anı Publishing, 2021)
The purpose of this embedded-single case study was to examine pre-service elementary teachers' noticing expertise of students' algebraic thinking in written works considering three skills: attention to students' solutions, interpretation of students' solutions, and deciding how to respond to students' solutions. The participants in this study involved 32 pre-service teachers who were enrolled at an Elementary Teacher Education Program in a public university in Turkey. The data were utilized by pre-service elementary teachers' responses to four students' solutions to a figural pattern task and were analyzed using the framework developed by Jacobs et al. (2010). The analysis indicated although the pre-service teachers could not provide robust evidence of attention and interpretation, they could be able to provide robust evidence of deciding how to respond. Specifically, the percentage of pre-service teachers demonstrating robust evidence was greatest in the skill of deciding how to respond, then interpreting, with attending having the lowest percentage of pre-service teachers demonstrating robust evidence.